2018
DOI: 10.1536/ihj.16-651
|View full text |Cite
|
Sign up to set email alerts
|

Various Cardiac Abnormalities Caused by Bacterial Myocarditis

Abstract: SummaryA 69-year-old woman without any past disease history was hospitalized for heart failure. After hospitalization, she showed myocardial infarction, atrioventricular dissociation, and cardiac dysfunction, and finally she passed away despite intensive care. Autopsy revealed that the cardiac abnormalities were due to bacterial myocarditis possibly resulting from urinary tract infection by E. coli. Although bacterial myocarditis is rare in developed countries, we should consider its possibility when patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…This infection is mainly caused by bacteria such as Staphylococcus aureus , Escherichia coli , Streptococcus, Pneumococcus , and Neisseria meningitides , which is also known as bacterial myocarditis. 3 Research shows that at least 50% of patients with septic shock are diagnosed as septic myocarditis, which is caused by myocardial dysfunction, indicating the poor prognosis of septic shock. 4 Our research group has found metformin could treat bacterial myocarditis in mice 5 not long ago, so we wondered whether it had the same positive effect on sepsis myocarditis in zebrafish.…”
Section: Introductionmentioning
confidence: 99%
“…This infection is mainly caused by bacteria such as Staphylococcus aureus , Escherichia coli , Streptococcus, Pneumococcus , and Neisseria meningitides , which is also known as bacterial myocarditis. 3 Research shows that at least 50% of patients with septic shock are diagnosed as septic myocarditis, which is caused by myocardial dysfunction, indicating the poor prognosis of septic shock. 4 Our research group has found metformin could treat bacterial myocarditis in mice 5 not long ago, so we wondered whether it had the same positive effect on sepsis myocarditis in zebrafish.…”
Section: Introductionmentioning
confidence: 99%
“…1) Direct viral invasion and indirect immunemediated myocardial injuries can both contribute to the development of myocarditis. 2) Acute fulminant myocarditis (AFM) is characterized by abrupt onset of cardiogenic shock, severe arrhythmia, and heart failure, which may lead to acute cardiac death in both pediatric and adult populations. 3,4) Despite modern advances in mechanical circulatory support, the in-hospital mortality of AFM remains high.…”
mentioning
confidence: 99%
“…In our patient, diffuse ST elevation on ECG may be precipitated by both septic shock and preexisting ischemic heart disease. Several possibilities and associated mechanisms have been proposed including direct bacterial invasion, bacterial toxins, and immune responses [7]. The differential diagnosis of acute bacterial myocarditis should be considered in this case because staphylococcus aureus was positive in both blood and urine cultures.…”
Section: Discussionmentioning
confidence: 92%